Language innovations in the formation of media image of Ukraine - Pliasun , Olga (Current issues of Ukrainian linguistics: theory and practice, 2021)
The article analyzes the influence of language innovations on the construction of state image. The author defines the term "language innovations" as new words and phraseologisms that appear and actively function in the modern media space and form the image of Ukraine. Emphasis is placed on the characteristics of the media sphere, which reproduces language innovations commensurate with the representative forms of the state image. The study singles out and systematically analyzes two vectors of influence of language innovations on the state image: 1) positive (therapeutic), associated with the development of new meanings of words, word-forming transformations, search for Ukrainian equivalents of borrowed lexemes, the emergence of new phraseologisms, evolution of youth slang, etc.; 2) negative (pathogenic), caused by destructive events in the economic, political, social spheres, the coronavirus pandemic, etc. The article proves that the positive image effect in the mass consciousness is created by the search for Ukrainian equivalents to borrowed lexemes, and not all of them are new. It is observed that the typical situation is the functioning of words in the media, which acquire a new meaning in mass communication. In addition, a positive author’s assessment of new words is of great importance in the popularization of Ukrainian neolexemes in the media. The study emphasizes that an effective linguistic tool for promoting language innovations in the language consciousness of Ukrainians is creolization, which affects the mass recipient not only verbally but also nonverbally, which creates a positive image effect. In terms of image therapy, the author considers the development of Ukrainian youth slang, computer jargon, some lexemes from the slang of social networks with neutral semantics. The author takes into account and interprets the material of innovative dictionaries "New words and phraseologisms in Ukrainian mass media" (New words and phraseologisms in Ukrainian mass media: a dictionary / L.I. Shevchenko, D.Yu. Syzonov; editor-in -chief L.I. Shevchenko. Kyiv, Kyiv University, 2017-2021). Attention is drawn to the accumulation of lexemes in image texts, the semantics of which are related to crimes in digital communication and motivated by information warfare, non-compliance with the principles of online security, etc., which has a pathogenic effect, discrediting the state image. The statement about the use of language innovations in media texts for the purpose of both positive (therapeutic) and negative (pathogenic) influence on the state image is concluding. To a large extent, this depends on the context in which the neolexeme is used, the author’s attitude to the described situation, as well as the level of media literacy, media education and critical thinking of the recipient of the media text.